Digital customer service and customer relationship management in last-mile logistics - Koh, Rou-An (Nanyang Technological University, 2022)
Purpose – This paper aims to identify the dimensions of service quality in last-mile logistics and examine their impact on customer satisfaction. Methodology/Approach – The indicators of service quality in last-mile logistics were identified by reviewing the literature. An online survey was then administered to 98 consumers of last-mile logistics in Singapore. Thereafter, exploratory factor analysis and partial least squares path modelling were conducted. Findings – Service quality in last-mile logistics can be represented by four key dimensions. In descending order of their impact on customer satisfaction, they are assurance, responsiveness, empathy and reliability. Service differentiation according to these results can be materialized to achieve greater customer satisfaction in last-mile logistics. Research Limitations/Implications – The allocation of resources by logistics firms to develop the level of service quality in last-mile logistics can be based on the new insights established in this study. Moreover, the developed research model for digital customer service quality can serve as a reference for firms to manage their relationships with customers. Originality/Value – An updated set of variables can now be utilized to represent service quality in the last-mile logistics industry. The paper also identifies the key drivers of customer satisfaction in digital customer relationship management. Keywords – Customer satisfaction, last-mile, customer relationship management Paper type – Research paper